2017
DOI: 10.1017/jfm.2017.589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a homogeneous magnetic field on the electrospraying characteristics of sulfolane ferrofluids

Abstract: We explore the effect of an applied homogeneous magnetic field on the electrospraying characteristics of a ferrofluid in the cone-jet mode. A sulfolane-based ferrofluid mixed with the ionic liquid ethyl ammonium nitrate has been synthesized. These mixtures have negligible volatility under ambient conditions and remain stable under a very wide range of electrical conductivities $K$. Magnetized Taylor cones spray with the same current emission characteristics as their non-magnetized counterparts in the shared vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The percentage of flowrate reduction was dependent on the amount of nanoparticles in the solution with a maximum of 43 percent reduction compared to the zero-magnetic-fieldminimum flowrate, when using a solution with 14.15 wt% nanoparticles. The reduction of the minimum flowrate aligns with studies on low-conductivity Sulfolane ferrofluids, 31 and should be further investigated to realize the interaction mechanism between the magnetic field and the high-conductivity ferrofluids.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…The percentage of flowrate reduction was dependent on the amount of nanoparticles in the solution with a maximum of 43 percent reduction compared to the zero-magnetic-fieldminimum flowrate, when using a solution with 14.15 wt% nanoparticles. The reduction of the minimum flowrate aligns with studies on low-conductivity Sulfolane ferrofluids, 31 and should be further investigated to realize the interaction mechanism between the magnetic field and the high-conductivity ferrofluids.…”
Section: Resultssupporting
confidence: 76%
“…Two forms of ILFF electrosprays have been studiedelectrospray from a "needle-free" ILFF peak formed by the Rosensweig instability, and electrospray from a capillary needle with and without an applied magnetic field. 31 Electrosprays from the Rosensweig instability have been produced from a single peak, 22,23,32 and an array of five peaks. [20][21][22] In each of these electrospray studies, dark residue on the extraction electrode revealed evidence of the magnetic nanoparticles.…”
Section: B Ionic Liquid Ferrofluid Electrospraysmentioning
confidence: 99%
See 2 more Smart Citations
“…Two forms of ILFF electrosprays have been studied -electrospray from a "needle-free" ILFF peak formed by the Rosensweig instability, and electrospray from a capillary needle with and without an applied magnetic field. 21 Electrosprays from the Rosensweig instability have been produced from a single peak, 13,20,22 and arrays of five, 10,11,20 seven, 23 and eight 23 peaks. In each of these electrospray studies, visual inspection of the residue from electrospray emission onto the extraction electrode revealed evidence of the magnetic nanoparticles.…”
Section: B Ionic Liquid Ferrofluid Electrospraysmentioning
confidence: 99%